PENGARUH VARIABEL MONETER (INFLASI, SUKU BUNGA, DAN NILAI TUKAR) TERHADAP PROFITABILITAS BANK PEMBANGUNAN DAERAH SEBELUM DAN SETELAH OTONOMI DAERAH (Studi Kasus Pada Bank Jatim, Bank Jateng dan Bank BJB Periode 1990-2012) - Gustiono, Restu (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aimsÂ  to show the effect of variable monetary (Inflation, Interest Rate, and Exchange Rate) on the profitability of Regional Development Banks Before and After Regional Autonomy. The data used is secondary data collected or gathered by researchers from various existing sources and processed with Panel Data regression. The population used in this study is the Regional Development Bank in Indonesia. By using purposive sampling method, a sample taken three Regional Development Banks.Based on the autocorrelation and heteroscedasticity test, there was no deviation from the classical assumptions. The results showed that there is a simultaneous influence of independent variables on the dependent variable in the period before and after regional autonomy. In addition, there is a partial significant influence on the variables Inflation and Interest Rate (before autonomy) and variable Inflation and Exchange Rate (after autonomy) to profitability or Return On Assets (ROA), Regional Development Banks.Keyword: Inflation, Interest Rate, Exchange Rate, ROA, Autonomy, BPD